Natural Language Processing (NLP) Technology for Chatbot Website - Agreianti Puspitasari; Astrid Noviana Paradhita; Yohanes Wien Tineka; Vivin Sulistyowati; Ni Komang Septia Noriska; Haryanto (Jurnal Penelitian Pendidikan IPA, 2024)
Chatbot technology is one form of application of Natural Language Processing, NLP is one of the branches of science Artificial Intelligence that studying communication between humans and computers through natural language. the purpose of this research will be carried out development of a chatbot application for information about the corporate, making it easier for visitors to find the information needed. This application built with a Natural Language Processing approach. This chatbot application uses medote text mining as a medium of reasoning. System modelling used for this application is using the Unified Model Language. The chatbot that will be developed is a website chatbot. The website chatbot was chosen by the company because one of the platforms that can be used well for export marketing is the website. This chatbot development uses Pyton, JavaScrib, Object notion (Json), Html + CSS. The application used in coding is Virtual Studio Code. Pyton is used to train a chatbot model that uses Natural Language Procecing (NLP). This Chatbot model is trained with the Neural Network Algorithm method, which is an algorithm model that is close to the human brain, which can provide stimulation or stimulation, process, and provide output to find relationships between data sets. JavaScrib is used to create chatbot data sets.